The effects of California's paid family leave program on mothers' leave-taking and subsequent labor market outcomes - Maya Rossin-Slater; Christopher J. Ruhm; Jane Waldfogel (Institute for the Study of Labor (IZA), 2011)
This analysis uses March Current Population Survey data from 1999-2010 and a differences-in-differences approach to examine how California's first in the nation paid family leave (PFL) program affected leave-taking by mothers following childbirth, as well as subsequent labor market outcomes. We obtain robust evidence that the California program more than doubled the overall use of maternity leave, increasing it from around three to six or seven weeks for the typical new mother - with particularly large growth for less advantaged groups. We also provide suggestive evidence that PFL increased the usual weekly work hours of employed mothers of one-to-three year-old children by 6 to 9% and that their wage incomes may have risen by a similar amount.
urn:nbn:de:101:1-201202285098
Keywords: J2; J13; J18; 330; parental leave; maternity leave; leave-taking; paid leave; maternal employment; Familienpolitik; Mütter; Mutterschutz; Lohnersatzleistungen; Arbeitsmarkt; Arbeitsangebot; Lohn; Kalifornien